Survey of In Situ Splitting Rib Harvesting Surgery for Orbital Deformity: Follow-Up. Issue 5 (July 2018) - Sun, Xiao-Ming; Ye, Ling-Xiao; Jin, Rong; Cheng, Li-Ying; Zhang, Ying; Zhang, Yu-Guang; Zhang, Lu
Abstract : Background: Our previous study indicated that in situ splitting rib harvesting surgery clinically reduced in related complications compared with the traditional surgical approach in the early stage, but there are few studies pay close attention to long-term recovery of donor area after rib harvesting. In this study, the authors conducted a follow-up study on recovery condition of donor and graft site of patients after in situ rib splitting grafting or simple whole rib grafting surgery. Methods: Between 2013 and 2016, 8 Chinese patients with orbital deformity were corrected using autogenous rib, of which 3 patients received conventional rib harvesting surgery, 3 patients received in situ splitting harvesting surgery, and 2 patients underwent both. In all patients, 3-dimensional computed tomography study of donor site and graft site were performed before and after operation. The ribs of donor site and graft site volume measurement were assessed using computed tomography 7 days and 12 months postoperation. Results: After 12 months operation, the integrity of rib arch recovered 94.1 ± 2.2% after in situ splitting rib harvesting, compared with 41.4 ± 5.0% after whole rib harvesting. The volume of grafted rib in situ splitting rib harvesting group reduced 69.8 ± 10.0% after 12 months operation compared with the volume after 1 week operation, and the reduced volume of ribs in whole rib harvesting group was 73.62 ± 9.5%. Conclusion: Rib regeneration occurred more quickly by in situ rib splitting harvesting approach compared with the traditional surgical approach.